Effects of high-intensity resistance circuit-based training in hypoxia on body composition and strength performance - Martinez-Guardado, I.; Ramos-Campo, D. J.; Olcina, G. J.; Rubio-Arias, J. A.; Chung, L. H.; Marin-Cascale, E. (European Journal of Sport Science, 2019)
Hypoxic training methods are increasingly being used by researchers in an attempt to improve performance in normoxic ambients. Moreover, previous research suggests that resistance training in hypoxia can cause physiological and muscle adaptations. The primary aim of this study was to compare the effects of 8 weeks of high-intensity resistance circuit-based (HRC) training in hypoxia on body composition and strength performance. The secondary aim was to examine the effects of HRC on metabolic parameters. Twenty-eight male participants were randomly assigned to either hypoxia (Fraction of inspired oxygen [FIO2] = 15%; HRChyp: n = 15; age: 24.6 ± 6.8 years; height: 177.4 ± 5.9 cm; weight: 74.9 ± 11.5 kg) or normoxia [FIO2] = 20.9%; HRCnorm: n = 13; age: 23.2 ± 5.2 years; height: 173.4 ± 6.2 cm; weight: 69.4 ± 7.4 kg) groups. Training sessions consisted of two blocks of three exercises (Block 1: bench press, leg extension and front pull down; Block 2: deadlift, elbow flexion and ankle extension). Each exercise was performed at six repetition maximum. Rest periods lasted for 35-s between exercises, 3-min between sets and 5-min between blocks. Participants exercised twice weekly for 8 weeks, and body composition, strength and blood tests were performed before and after the training program. Lean body mass and bone mineral density significantly increased over time in the HRChyp (p < .005; ES = 0.14 and p < .014; ES = 0.19, respectively) but not in the HRCnorm after training. Both groups improved their strength performance over time (p < .001), but without group effect differences. These results indicate that simulated hypoxia during HRC exercise produced trivial effects on lean body mass and bone mineral density compared to normoxia.